2003
DOI: 10.1590/s1516-89132003000400008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the SPD and the SPDS methods for segregating generation advancement in soybean

Abstract: The purpose of this work was to compare the SPD (Single Pod Descent) and SPDS (Single Pod Descent with Selection) methods for segregating generation advancement in soybean breeding. Sixteen populations derived from crosses among Japanese and adapted Brazilian soybean were used. The traits, number of days to flowering (NDF) and to maturity (NDM), plant height at flowering (PHF) and at maturity (PHM), and individual plant yield (IPY) were assessed. The populations obtained by SPDS showed values close to the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
6
0
2
Order By: Relevance
“…A further modification introduces selection against inferior genotypes during single pod descent. Single pod descent with selection, in this case for maturity, was found desirable since it reduced the size of the population advanced and produced superior lines (Destro et al 2003). In a similar study pedigree selection, single seed descent, and single seed descent with selection for early maturity were compared, and single seed descent with selection was found to be the most costeffective (Byron and Orf 1991).…”
Section: Advancing Toward Homozygositymentioning
confidence: 99%
“…A further modification introduces selection against inferior genotypes during single pod descent. Single pod descent with selection, in this case for maturity, was found desirable since it reduced the size of the population advanced and produced superior lines (Destro et al 2003). In a similar study pedigree selection, single seed descent, and single seed descent with selection for early maturity were compared, and single seed descent with selection was found to be the most costeffective (Byron and Orf 1991).…”
Section: Advancing Toward Homozygositymentioning
confidence: 99%
“…Different selection methods used for the identification of desirable traits are the pedigree, single-seed descent, mass selection, and bulk methods (Allard, 2014). In addition, modified selection methods have also been developed and applied elsewhere (Toledo et al, 1994;Destro et al, 2003;Miladinovic et al, 2011). Progress in plant breeding largely depends on the skill of the breeder in identifying selection criteria and applying selection methods that are able to promote the desired changes in characteristics of interest in a breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used for selection of grain yield in segregating populations have been compared in various crops such as soybean (Destro et al, 2003;Miladinović et al, 2011;Funada et al, 2013), common bean (Raposo et al, 2000;Costa et al, 2002), cowpea (Mehta and Zaveri, 2000), chickpea (Meena and Kumar, 2012), barley (Lalić et al, 2003), sesame (Vinayan and Govindarasu, 2010), cauliflower (Chigeza et al, 2013), and rice (Fahim et al, 1998;Ntanos and Roupakias, 2001;Kanbar et al, 2011). Most of these studies showed significant differences between the methods used for developing superior progenies or lines.…”
Section: Introductionmentioning
confidence: 99%